Flavonoid composition, cellular antioxidant activity and (myelo)peroxidase inhibition of a Bryonia alba L. (Cucurbitaceae) leaves extract. (15th October 2018) - Ielciu, Irina; Mouithys-Mickalad, Ange; Franck, Thierry; Angenot, Luc; Ledoux, Allison; Păltinean, Ramona; Cieckiewicz, Ewa; Etienne, Delphine; Tits, Monique; Crişan, Gianina; Frédérich, Michel
Abstract: Objectives: The aim of the present study consisted in the isolation of flavonoids from the leaves of Bryonia alba L. and evaluation of their antioxidant activity and inhibition on peroxidase-catalysed reactions. Methods: Flavonoids were isolated by preparative HPLC-DAD and their structures were elucidated by MS and NMR. Inhibitory effect was tested by the horseradish peroxidase and the myeloperoxidase assays. Cellular antioxidant assays consisted in testing the inhibitory activity on the reactive oxygen species released upon activation of neutrophils freshly isolated ex vivo from equine blood and of human monocytes-derived macrophages in vitro . Whole organism toxicity was assessed on zebrafish larvae. Key findings: Four flavonoids (lutonarin, saponarin, isoorientin and isovitexin) were isolated. The performed assays showed significant antioxidant activity and inhibition for the peroxidase-catalysed reactions. Absence of cellular and zebrafish toxicity was confirmed. Conclusions: Bryonia alba L. leaves are particularly interesting for their flavonoids content and showed significant inhibitory effect on peroxidase-catalysed oxidation of substrates (Amplex Red and L012), as well as antioxidant/antiradical activity, proving that this species has a medicinal potential. Moreover, the present study highlights the absence of the toxicity of these leaves and offers though a novel perspective on the species, previously known as being toxic.